Formulation of Insulin Self Nanoemulsifying Drug Delivery System and Its In Vitro-In Vivo Study - Lina Winarti; Suwaldi Suwaldi; Ronny Martien; Lukman Hakim (Indonesian Journal of Pharmacy, 2018)
Particulate delivery system can be used for improving the efficacy of protein and peptide drug. In addition to a polymer-based particulate delivery system, self-nanoemulsifying drug delivery system (SNEDDS), a lipid-based delivery system, is currently developed for either less water-soluble or soluble drugs. This study aims to design SNEDDS for oral insulin administration and its in vitro-in vivo study. The SNEDDS template was designed using D-optimal mixture design and was analyzed using software Design Expert 7.1.5. The obtained optimum template was loaded with insulin and evaluated for its transmittance percentage, emulsification time, particle size, zeta potential, stability, the amount of insulin in vitro diffused across rat intestine, and insulin serum concentration after oral administration. The study results revealed that the optimum template of SNEDDS formula consisted of 10% (w/w) Miglyol 812N, 65% (w/w) Tween 80, and 25% (w/w) propylene glycol. These optimum template then was loaded with insulin and characterized. SNEDDS insulin has particle size of 12.0±1.7 nm, zeta potential of +0.16mV, transmittance of >90%, and emulsification time of < 60 seconds. The stability study showed that SNEDDS insulin was stable from both precipitation and phase separation. The amount of insulin transported from SNEDDS formula in vitro was 32.45±2.03% and non-SNEDDS formula was 10.44±5.04%. In vivo study of SNEDDS insulin produced a significantly increased Cmax, AUC, and F value than insulin non SNEDDS (p < 0.05). In brief, SNEDDS formulation in this study is a promising approach to increase the effectiveness of oral insulin. Insulin is better given orally in SNEDDS formulation than in non SNEDDS formulation.